Building Application-Related Patient Identifiers: What Solution for a European Country? - Catherine Quantin; François-André Allaert; Paul Avillach; Maniane Fassa; Benoît Riandey; Gilles Trouessin; Olivier Cohen (International Journal of Telemedicine and Applications)
We propose a method utilizing a derived social security number with the same reliability as the social security number. We show the anonymity techniques classically based on unidirectional hash functions (such as the secure hash algorithm (SHA-2) function that can guarantee the security, quality, and reliability of information if these techniques are applied to the Social Security Number). Hashing produces a strictly anonymous code that is always the same for a given individual, and thus enables patient data to be linked. Different solutions are developed and proposed in this article. Hashing the social security number will make it possible to link the information in the personal medical file to other national health information sources with the aim of completing or validating the personal medical record or conducting epidemiological and clinical research. This data linkage would meet the anonymous data requirements of the European directive on data protection.